Child Labor, Urban Proximity, and Household Composition. - Fafchamps, M; Wahba, J (Department of Economics (University of Oxford), 2004)
Using detailed survey data from Nepal, this paper examines the determinants of child labor with a special emphasis on urban proximity. We …nd that children residing in or near urban centers attend school more and work less in total but are more likely to be involved in wage work or in a small business. The larger the urban center, the stronger the e¤ect is. Urban proximity is found to reduce the workload of children and improve school attendance up to 3 hours of travel time from the city. In areas of commercialized agriculture located 5 to 8 hours from the city, children do more farm work. Children unrelated or loosely related to the household head work more, especially in market work and household chores, and are less likely to attend school. This is especially true of child servants, a small group who appear particularly at risk.